A Study on the Outcome Parameters of Benign Prostate Hyperplasia Patients with Prostatic Inflammation after Turp - Tanveer Ahmad, Numan Alam, Sami Ullah, Sikandar Ali, Abdullah Shaikh, Shahjehan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the outcome parameters of benign prostate hyperplasia patients with prostatic inflammation Material and methods: An observational study was conducted on 60 patients at different centres including Urology Unit, Waseem Medical Centre Batkhaila District Malakand, KPK and Department of Surgery, DHQ Hospital Mardan, KPK in the duration from October, 2022 to March, 2023. Patients presented with BPH with prostatic inflammation undergoing TURP were assessed for various clinical parameters. Paired samples T test was applied to assess pre and postoperative clinical parameters. Results: The mean age of the patients was 64.88±6.48 years. Significant improvement was observed in the outcome clinical parameters before and after surgery using the paired samples T test. Conclusion: Transurethral resection of the prostate in patients with BPH with prostatic inflammation yields significantly improved post-operative outcomes. Keywords: Transurethral resection of the prostate, Benign prostatic hyperplasia, prostatic inflammation.